(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2011)
The text analyzes scientific experimentation on human beings, presenting the entire historical evolution of this research and highlighting the importance of the documents that served as the basis for the current regulation of the subject. It looks at the limits of research, relating them to the principles of bioethics: autonomy, beneficence, non-maleficence and justice. It also deals with research involving vulnerable people, such as the unborn, children, adolescents, pregnant women and nursing mothers, as well as research involving vulnerable groups.